Successful management of a rare radius schwannoma mimicking malignant bone tumors: A case report and literature review - Sun, Nianzhe; Khan, Umar Zeb; Zeng, Lei; Wu, Panfeng; Xiong, Qin; Peng, Lushan; Yu, Hong; Tang, Juyu (Frontiers in Surgery, 2023)
Background Schwannomas are benign tumors originating from Schwann cells, frequently occurring in the spinal cord and peripheral nerves. Intraosseous schwannomas, a rare subset, account for approximately 0.2% of schwannomas. Intraosseous schwannomas commonly impinge the mandible, followed by the sacrum and the spine. By far, only three cases of radius intraosseous schwannomas have been reported in PubMed. The tumor was treated differently in all three cases, resulting in different outcomes. Case presentation A 29-year-old male construction engineer who complained of a painless mass on the radial aspect of the right forearm was diagnosed with an intraosseous schwannoma of the radius based on radiography, three-dimensional computed tomography reconstruction, magnetic resonance imaging, pathological examination, and immunohistochemistry. A different surgical approach was employed to reconstruct the radial graft defect using bone microrepair techniques, resulting in more reliable bone healing and early functional recovery. Meanwhile, no clinical and radiographic findings suggestive of recurrence were observed at the 12-month follow-up. Conclusion Vascularized bone flap transplantation combined with three-dimensional imaging reconstruction planning might yield better results for repairing small segmental bone defects of the radius caused by intraosseous schwannomas.